Evaluation of Canal Transportation after Using Different Types Rotary Glide Path Files - Shalan, Linz Ali; Al-Huwaizi, Hussain F (Iranian Endodontic Journal, 2018)
Introduction: Canal transportation is a common problem caused by rotary instruments. The purpose of the present study was to evaluate root canal transportation after using WaveOne Gold Glider, ProGlider, Path File and K-file. Methods and materials: Forty resin blocks with L-shaped canals were divided into four groups (n=10). Group 1; canals were prepared with WaveOne Gold Glider, group 2; ProGlider, group 3; Path Files and group 4; #10, #15, and #20 stainless steel manual K-Files. Pre- and post-instrumentation photographic images were superimposed and resin removed from the inner and outer surfaces of the root canal was calculated through 3 points at 3, 6 and 9 mm from the end of canal which represented canal transportation. All data were analyzed by one way ANOVA test. The level of significance was set at 0.05. Results: Statistical analysis by one-way ANOVA test revealed that there was no significant differences (P>0.05) between the tested files in canal transportation in apical, middle and coronal third. The last amount of canal transportation happened at the apical third in WaveOne Gold Glider group. Conclusions: This in vitro study showed that using WaveOne Gold Glider files lead to less canal transportation especially in the apical third area with less significant differences with ProGlider, PathFiles and K-File. Keywords: Canal Transportation; Glide Path File; Resin Block; WaveOne Gold Glider